The Influence of Financial Knowledge, Financial Attitude, Locus of Control and Income on Financial Management Behavior in Culinary Sub-Sector MSMEs in Trawas District - Sus Anisa; Hartono; Rini Armin (CV Putra Publisher, 2023)
This study aims to determine the extent to which financial knowledge, financial attitude, locus of control and income influence the behavior of financial management in Culinary Sub-Sector SMEs in Trawas District. The method used in this study is a quantitative method with descriptive analysis based on primary data obtained directly through distributing questionnaires and secondary data obtained from related parties, interviews, books and journals, etc. This research was conducted by distributing questionnaires to respondents. The population in this study are MSME actors in the Culinary Sub Sector in Trawas District. While the sample used is 50 MSMEs with the criteria of MSMEs being in Taman Ghanjaran, 3 years old and active until now in 2023. The sampling technique used is purposive sampling. The results of this study show that financial knowledge, financial attitude and locus of control partially have a significant effect on financial management behavior. Meanwhile, income partially has no significant effect on financial management behavior. Simultaneously (f test) shows that financial knowledge, financial attitude, locus of control and income simultaneously have a significant effect on financial management behavior.